The Hearing of Sufism - Mahloube, Brhan; Ali, Maissa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
In addition to their different directions and schools’sufis cared for what called: sufism’s hearing and dancing ,in indication to the importance of hearing as a basic phenomenon with important role of making the spirtitualesufism experience.that what make the sufis believe that the hearing create love and passion of desire to haven and to the kingdom of good. Then prepare willer to be recalled by holly presence of god to embrasse the absolution ,then bring him back to himself to reveale the spiritual trouth with in it . Hearing usually be attended with dancing moves wich intensify the joining group of dance.thus reveal the relation between the material and the spiritual in the willer soul. This report offer abrief idea of soufism hearing and dancing and clearify the joining and vanishing among the holly spirit wich we can observe clearly in MAWLAWYA way founded by JALAL AL DDIN ALROUMI.